Acupuncture-like transcutaneous nerve stimulation therapy success after 5 years post-radiation-induced xerostomia: a case report. Issue 2 (11th January 2016) - Patel-Yadav, Ami; Singh, Anurag
Abstract: Background: Success with acupuncture-like transcutaneous nerve stimulation (ALTENS) in the treatment of radiation-induced xerostomia has not been reported after an extended time. Methods: We report a case of successful ALTENS therapy 5 years after radiation treatment. Results: The patient discontinued treatments in a second course due to complete resolution of symptoms. Conclusion: This case report demonstrates a potential for offering ALTENS to those long suffering from radiation-induced xerostomia.